Synoptic Associations of Winter Climate and Snowfall Variability in New England, USA, 1950-1992 - Hartley, Suzanne; Keables, Michael J. (Scholarworks @ Morehead State, 1998)
Seasonal snowfall in New England has exhibited wide variations over the last few decades, the underlying causes of which have not been identified previously. In this paper, compositing and statistical analyses examine how interactions among the large-scale atmospheric circulation, cyclonic activity and storm track preferences, and western Atlantic sea-surface temperatures contribute to winter climate variability and exceptional winter snowfall totals in New England. High winter snowfall totals are associated with a meridional circulation regime, as indicated by a negative North Atlantic Oscillation (NAO) index and negative 700 hPa height anomalies over the eastern USA.Anomalously high surface pressure over northern Canada promotes advection of cold air into the region, and the preferred storm track is along or just to the south of the New England coast. Low winter snowfall totals are associated with no unique set of circumstances, but a positive NAO index and more zonal circulation is indicated,along with a weaker surface high over Canada, and a storm track over interior New England rather than along the coast. There is no direct association with the Pacific – North American index, although this may modulate the association with the NAO. In extreme southern New England, high (low) winter snowfall totals are associated with negative (positive) sea-surface temperature anomalies along the Atlantic seaboard.